Hubungan Tingkat Pendidikan Terhadap Tingkat Pengetahuan Masyarakat Tentang Obat Tradisional di RT 05 Desa Karanggayam, Bantul - Urfiyya, Qarriy 'Aina (Jurnal Inovasi Farmasi Indonesia (JAFI), 2023)
Traditional medicine has been widely used around the world and in Indonesia, but the public knowledge is still limited. As many as 92% of Indonesians stated that they knew about traditional medicine, but limited about jamu. This study aimed to determine the association between the level of education and the level of community knowledge about traditional medicine in RT 05 Karanggayam Bantul village. This study used an observational analytic method with cross sectional approach. The sampling technique used purposive sampling of 75 respondents. Data analysis was carried out on the characteristics of respondents, the level of knowledge and the association between the level of education and the level of knowledge using the Kruskal-wallis test. The results obtained from the level of knowledge about traditional medicine in the good category amounted to 48%, enough by 35%, and less by 17%. The Kruskal-Wallis test results obtained a p value of 0.322. The conclusion of this study is that there is no association between education level and the level of community knowledge about traditional medicine in RT 05 Karanggayam Bantul Village.